Approximate solution of a model describing biological species living together using a new iterative method - AL-Jawary, Majeed (International Journal of Applied Mathematical Research, 2014)
In the present article, we implement the new iterative method proposed by Daftardar-Gejji and Jafari (NIM or DJM) [V. Daftardar-Gejji, H. Jafari, An iterative method for solving non linear functional equations, J. Math. Anal. Appl. 316 (2006) 753-763] to solve a system of two nonlinear integro-differential equations, which describes biological species living together. The results demonstrate that the method has many merits such as being derivative-free, can be easily comprehended with only a basic knowledge of Calculus. Also, the DJM overcoming the difficulty arising in calculating Adomian polynomials to handle the nonlinear terms in Adomian Decomposition Method (ADM). Does not require to calculate Lagrange multiplier as in Variational Iteration Method (VIM) and no needs to construct a homotopy as in Homotopy Perturbation Method (HPM) that implemented to solve the problem. Numerical examples are presented for several problems, to demonstrate the efficiency of the proposed method. A comparison with some existing techniques such as ADM, HPM and VIM also presented, which shows that the DJM is effective and convenient to use and overcomes the difficulties arising in existing techniques. The software used for the calculations in this study was MATHEMATICA®8.0.Keywords: Biological species living together, Integro-differential equation, Mathematical biology, New iterative method.